Phytochemical and Pharmacological Potential of Lantana Camara Linn: Pharmaceutical Science-Pharmacognosy - Naphade, Vaishali; S. Bhamre, Jayesh; M. Avaghade, Manoj; S. Kale, Mansi; R. Bendale, Atul; L. Borse, Sandhya; B. Borse, Laxmikant (International Journal of Life Science and Pharma Research, 2023)
Traditional medicine and medicinal plants, as well as their study of modern chemical principles, may lead to the creation of newer and less expensive medications. This overview incorporates all aspects of Lantana camara Linn that other papers have overlooked. Lantana camara Linn is also a widespread weed and a famous ornamental plant. It is noteworthy that plants have long been an excellent source of medicine. Lantana camara (L. camara) is well-known for its many ailments, such as cuts, inflammation, ulcers, cataract, itching, eczema, and arthritis. Various parts of the Lantana camara plant are used medicinally for colds, coughs, pox, bronchitis, and hypertension. In addition, L. camara scientifically studied various therapeutic activities such as antibacterial, antioxidant, antipyretic, larvicidal, antifungal etc. Over the past few decades, scientists and researchers worldwide have expanded their knowledge and studied the chemical composition of the entire L-plant and their medical activities. It is also known as a plant that produces essential oil, and essential oils are available in the market, known as Lantana oil. The phytoconstituents found in all portions of L. camara have been documented in various publications. Over the last few decades, scientists and researchers worldwide have thoroughly investigated the chemical content of the entire L. camara plant. The plant is widespread in Uttarakhand, Uttar Pradesh, Himachal Pradesh, and India's north-eastern provinces. This paper examined the phytochemicals found in L. camara. The review focuses on this plant's traditional usage, chemical constituents, pharmacological activity, and toxicology and other potential uses. This study aims to provide a comprehensive report on the literature on its phytochemistry and pharmacological action.